Use of clitic pronouns in aphasic speakers with agrammatism. A study from Spanish - Guillén Escamilla, Josaphat Enrique; Arias García, Mónica; Téllez Lamegos, Jesús (Revista de Investigación en Logopedia, 2022)
Agrammatism is a symptom of the no-fluent aphasias. It is manifested mainly by omission of function words and inflectional and derivational affixes. In this context, clitics pronouns have been broadly analyzed and it has been concluded that exist an alteration in its production too. Despite, these studies take as start point a narrow syntactic criterion and use test ad hoc which do not reflect speakers’ real abilities to employ linguistic system. Thus, the main aim of this research is analyzing use of clitics pronouns in communicative environments more realistic to determine if in these scenarios clitics are altered too. To do this, Corpus PerLA’s volume Afasia no fluente (Gallardo y Moreno, 2005) was analyzed. Results point out that speakers have very few problems to correctly use clitics and errors are due by omissions of verbs. It is concluded that this contrast with the previous results is due to the nature of our corpus, as it better reflects the preserved abilities of the patients.